Sol-gel-derived ZnO:Mn nanocrystals: Study of structural, Raman, and optical properties - Kumar S.; Chatterjee S.; Chattopadhyay K.K.; Ghosh A.K. (My University, 2025)
Structural, Raman, and optical properties of sol-gel derived Zn 1-xMn xO (0≤x ≤ 0.06) nanoparticles have been investigated. The crystallite structure, morphology, and size estimation have been performed by X-ray diffraction (XRD) and high-resolution transmission electron microscopy (HRTEM). To study the crystalline quality, structural disorder and defects in the host lattice, we have employed Raman Spectroscopy. The wurtzite structure and formation of tetrahedral coordination of the oxygen ions surrounding the zinc ions has been confirmed by FTIR analysis. Optical properties have been studied by UV-vis and PL spectroscopy. UV-vis measurements show that the band gap is increased with increasing Mn concentration. This may be attributed to the orbital hybridizations that are prevailed throughout the whole range of Mn doping. Variation of resistivity with temperature shows that thermally activated conduction (Arrhenius) mechanism is valid in the high-temperature region (T > 250 K), whereas Mott's variable-range hopping (VRH) mechanism is valid in low-temperature region (T < 250 K). Variation of the activation energy estimated from the resistivity measurement (Arrhenius law) qualitatively follows the variation of the optical band gap. © 2012 American Chemical Society.